What is Simplifying?

Look carefully, the 1st step is veryyyyyy Long and complicated

and the final answer is veryyyyy short and Simple.

"Simple and Short make it Sweet"

[2(x + 5y) - 3(x-y)] - 7[3x-(x+6y)]

= [2x + 10y - 3x + 3y] - 7[3x - x - 6y]

= [2x - 3x + 10y + 3y] - 7[2x - 6y]

= [ -x + 13y ] - 14x + 42y

= - x + 13y - 14x + 42y

= 42y + 13y -14x -x

= 55y - 15x

Basically, to simplify an equation you just need to

words in the bracket and you will master in just a few minutes!Look carefully, the 1st step is veryyyyyy Long and complicated

and the final answer is veryyyyy short and Simple.

"Simple and Short make it Sweet"

[2(x + 5y) - 3(x-y)] - 7[3x-(x+6y)]

= [2x + 10y - 3x + 3y] - 7[3x - x - 6y]

= [2x - 3x + 10y + 3y] - 7[2x - 6y]

= [ -x + 13y ] - 14x + 42y

= - x + 13y - 14x + 42y

= 42y + 13y -14x -x

= 55y - 15x

**CONCLUSION:**Basically, to simplify an equation you just need to

**understand**the following**"Inner to Outer, Left to Right" (Filomaths' mantra)**

**- Expansion Mantra: "Sign with Sign, No with No, Alpha with Alpha" (Modification)**

**- Arrangement Mantra: "x with x, x*2 with x*2, y with y and so on..." (Modification)**

**- Simplifying (Combination)**

**Find out more about filomaths,**

**by making an appointment with our Founder, Mr K L Chua,**

**to have a Casual Talk with him Today!**

*.*
## No comments :

## Post a Comment